On some conceptual pitfalls of the teaching of values in the age of relativism = O niektórych konceptualnych pułapkach nauczania wartości w epoce relatywizmu - Strouhal, Martin (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The text deals with the question about the extent to which the concept of value and the value orientation in the contemporary pedagogical thought corresponds with philosophical and ideal intentions. The question is how reality approaches the ideal and what meaning this has for man. The aim of the text is to draw attention to the need to clarify the vocabulary which is used in the theory and practice of teaching of values in the era of deepening relativism.
Keywords: theory of education; values; value education; ideal; relativism; teoria edukacji; wartości; wartość edukacji; ideał; relatywizm